Improved markerless gait kinematics measurement using a biomechanically-aware algorithm with subject-specific geometric modeling - Hatamzadeh, Mehran; Busé, Laurent; Turcot, Katia; Zory, Raphael (Measurement : journal of the International Measurement Confederation, 2024)
•An algorithm to improve kinematics accuracy in markerless gait analysis is presented.•This algorithm refines AI-driven skeletons in a subject-specific geometric manner.•It preserves skeleton links’ length during walking, using intra-frame modelization.•It benefits from gait phases information in between-frames adjustments.•It smooths lower limb joints’ trajectory in between-frames adjustments. Despite the advancements in developing markerless gait analysis systems, they still demonstrate lower accuracy compared to gold-standard systems. Hence, in this research, a novel approach is presented to improve the lower limb kinematics accuracy in markerless gait analysis. This approach refines the 3D lower-limb skeletons obtained by AI-based pose estimation algorithms in a subject-specific geometric manner, preserves skeleton links’ length, benefits from gait phases information that adds biomechanical awareness to the algorithm, and utilizes an embedded trajectory smoothing. Validation of the proposed method shows that it reduces 12.6–43.5 % of root mean square error (RMSE) and significantly improves kinematic curves’ similarity to the gold-standard ones. Results also prove the feasibility of more accurate lower limb kinematics calculation using a single (2.02–7.57° RMSE) or dual RGB-D camera (1.66–7.25° RMSE). Development of such algorithms could result in requirement of fewer cameras that deliver comparable or even superior measurement accuracy compared to multi-camera approaches.